MoDELS 2007 Doctoral Symposium summary - Sin autor (^p Datos electrónicos (1 archivo : 113 KB))
The MoDELS 2007 Doctoral Symposium provided a forum for Ph.D. students, conducting research in model-driven software engineering, to discuss their goals, methodology and results at an early stage in their research, in a critical but supportive and constructive environment. The symposium offered an opportunity for the eight student participants to interact with other students at a similar stage in their careers and with the mentoring board composed of five experts in the software modeling field. The students received practical guidance for the completion of the dissertation research and motivation for a research career. This summary offers an overview of the activities that occurred at the Symposium.